Current Status of Cardiovascular Disease According to the Duration of Hypertension in Korean Adults - Byoung Geol Choi; Jung Boone Kim; Seung-Woon Rha; Min Woo Lee; Michael S. Lee; Suhng Wook Kim; Sunghoi Hong (Ubiquity Press, 2023)
Background: Today, medical technology and healthcare advances have led to an increased life expectancy; however, the prevalence of chronic diseases such as hypertension, diabetes mellitus, stroke, and cardiovascular events is continuously rising. In particular, hypertension is a crucial factor in cardiovascular and cerebrovascular diseases, and it is known that prevention and management are essential. Objectives: This study investigates the prevalence and management of hypertension in Korean adults and evaluates its correlation with the risk of cardiovascular disease (CVD) and stroke. Method: The Korean National Health and Nutritional Examination Survey (KNHANES) database was utilized for this study (https://knhanes.cdc.go.kr). The subjects of this survey were sampled to represent the entire population of Korea. The study aims to assess the risk of CVD and stroke according to the duration of hypertension. We also examined the impact of hypertension control on the risk of CVD and stroke. This study is a retrospective cross-sectional study, so future risks cannot be assessed, but only the disease status at the same time point. Results: A total of 61,379 subjects were enrolled in the KNHANES database, representing Korea's population of 49,068,178 subjects. The prevalence of hypertension was 25.7% (9,965,618 subjects) of the total population. The prevalence of hypertension increased rapidly with the age of the population. As the duration of hypertension increased, the risks of CVD and stroke also increased. When hypertension lasts longer than 20 years, ischemic heart disease, myocardial infarction, and stroke prevalence were 14.6%, 5.0%, and 12.2%, respectively. However, achieving a target blood pressure (BP) goal below 140/90 mmHg reduced the risk of all CVD and stroke by nearly half. Nevertheless, fewer than two-thirds of patients in Korea with hypertension achieved this targeted blood pressure goal. Conclusions: Our study confirmed that the prevalence of hypertension in Korean adults was higher than a quarter but also showed that the risk of CVD and stroke was significantly reduced by achieving optimal blood pressure control. Based on these results, policy efforts are needed to reach the target BP and improve the treatment rates for hypertension in Korea.